Mesalazine: A Novel Etiology For Drug-Induced Urinary Calculi - Corbery, Blaise; Lebdai, Souhil; Borojeni, Shahed; Bigot, Pierre; Azzouzi, Abdel-Rahmène; Culty, Thibaut (Urology Journal, 2018)
We report the case of a 23-year-old woman treated by mesalazine for ulcerative colitis and who subsequently presented recurrent renal colic due to mesalazine urinary stones. This is the second case described in the literature. Mesalazine stones are soft, friable and have an orange-beige color. They are not visible on non-contrast computed tomography (CT). Their diagnosis is based on morpho-constitutional analysis and CT-urography. Patients treated by mesalazine who present renal colic should undergo CT-urography in order to make the diagnosis.